Long-range magnetic coupling across a polar insulating layer - COEY, JOHN; VENKATESAN, MUNUSWAMY (My University, 2016)
Magnetic interactions in solids are normally mediated by short-range exchange or weak dipole fields. Here we report a magnetic interaction that can propagate over long distances (∼10 nm) across a polar insulating oxide spacer. Evidence includes oscillations of magnetization, coercivity and field-cooled loop shift with the thickness of LaAlO3 in La0.67Sr0.33MnO3/LaAlO3/SrTiO3 heterostructures. Similar modifications of the hysteresis loop appear when two coupled films of La0.67Sr0.33MnO3 are separated by LaAlO3, or another polar insulator, but they are absent when the oxide spacer layer is nonpolar. The loop shift is attributed to strong spin–orbit coupling and Dzyaloshinskii–Moriya interaction at the interfaces. There is evidence from inelastic light scattering that the polar spacer mediates long-range transmission of orbital magnetization. This coupling mechanism is expected to apply for any conducting ferromagnetic oxide with mixed valence; in view of electron hopping frequency involved, it raises the prospect of terahertz tunability of magnetic coupling.
PUBLISHED
Cited By :3 Export Date: 13 January 2017
Keywords: Magnetic interactions; Magnetic interactions